PENGARUH ORIENTASI PASAR DAN INOVASI TERHADAP KEUNGGULAN BERSAING DAN KINERJA PEMASARAN - Kencana, Putu Aryanti Putri; Giantari, I Gusti Ayu Ketut (Buletin Studi Ekonomi; VOL.26.NO.2.AGUSTUS 2021DO - 10.24843/BSE.2021.v26.i02.p03, 2021)
The purpose of this research is to explain the influence of market orientation and innovation on competitive advantages and marketing performance on apparel MSMEs in Denpasar City. This research was conducted in MSME apparel located in Denpasar city with a sample of 50 MSMEs using purposive sampling sample determination method. Data collection using questionnaires. The data were analyzed using PLS-based SEM analysis techniques. The results of this study showed that market orientation has a positive and significant effect on marketing performance, innovation positively and significantly affects marketing performance, market orientation has a positive and significant effect on competitive excellence, innovation positively and significantly affects competitive excellence, competitive advantage has a positive and significant effect on marketing performance.